Listeria monocytogenes and other Listeria species in small and very small ready-to-eat meat processing plants - Williams, Shanna Kellyn, author; Nightingale, Kendra, advisor; Sofos, John Nikolaos, committee member; Hyatt, Doreene, committee member (Colorado State University. Libraries, 2010)
Listeria monocytogenes is the causative agent of listeriosis, a severe foodborne disease associated with a high case fatality rate. To prevent product contamination with L. monocytogenes, it is crucial to understand Listeria contamination patterns in the food processing plant environment. The aim of this study was to monitor Listeria contamination patterns for two years in six small or very small ready-to-eat (RTE) meat processing plants using a routine combined cultural and molecular typing program. Each of the six plants enrolled in the study were visited on a bi-monthly basis for a two-year period where samples were collected, microbiologically analyzed for Listeria and isolates from positive samples were characterized by molecular subtyping. Year one of the project focused only on non-food contact environmental samples within each plant, and year two focused again on non-food contact environmental samples as well as food contact surfaces and finished RTE meat product samples from participating plants. Between year one and year two of sampling, we conducted an in-plant training session involving all employees at each plant. During this training session, we informed employees about general Listeria knowledge such as ecology, transmission and control strategies. Also, we informed each plant of the testing and molecular subtyping results obtained in the first year of the study. Employees also were given a pre- and post-training evaluation, which included 23 questions on Listeria, to probe knowledge gained through the training session. A common characteristic among almost all plants enrolled in our study was the persistence of a single or few predominant L. monocytogenes and/or other Listeria spp. molecular subtype(s) in the plant environment. Identification of persistent strains and their associated harborage sites in the environment of each plant highlight the continued need for adequate cleaning and sanitation practices to eliminate harborage sites and reduce the risk of transmission to the finished product. Interestingly, we not only observed a significant increase in plant employee knowledge regarding Listeria following the in-plant training sessions, but we also detected a significant decrease in Listeria contamination across all six plants when comparing testing results from year 1 and 2. With combined molecular detection and subtyping, we were able to help increase plant awareness about Listeria contamination patterns, identify harborage sites and intervention strategies to better control Listeria in the plant environment.
Keywords: Listeria monocytogenes; Food contamination; Meat -- Contamination; Ready meals; Food -- Safety measures